Continuous Monitoring of Serum Markers for Early Detection of Periprosthetic Joint Infection in Osteoporotic Patients Undergoing Hip Arthroplasty: A Prospective Cohort Study: Inflammatory markers, matrix metalloproteinase-9 (MMP-9), and serum amyloid A, PCT, D-dimer - Sun, Yongming (Journal of Medical Biochemistry, 2025)
Background: Periprosthetic joint infection (PJI) is a significant complication following hip arthroplasty, especially in osteoporotic patients. Early detection is crucial for improving outcomes, but remains challenging. This study assesses the effectiveness of continuous monitoring of serum markers—C-reactive protein (CRP), procalcitonin (PCT), erythrocyte sedimentation rate (ESR), D-dimer, white blood cell count (WBC), ferritin, soluble CD14 (sCD14), matrix metalloproteinase-9 (MMP-9), and serum amyloid A (SAA)—for early detection of PJI in osteoporotic patients undergoing hip arthroplasty. Methods: A prospective cohort study included 150 osteoporotic patients undergoing hip arthroplasty. Inflammatory markers were measured preoperatively and at 24-, 48-, and 72-hours post-surgery, with weekly follow-ups for 6 weeks. PJI was diagnosed based on clinical, microbiological, and imaging criteria. Diagnostic performance of individual markers was assessed using Receiver Operating Characteristic (ROC) curves. Results: Among the 150 patients, 12 (8%) developed PJI within 6 weeks. At 48 hours post-surgery, CRP, PCT, ESR, D-dimer, WBC, sCD14, and SAA were significantly higher in the PJI group compared to the non-infected group (p<0.05 for all). Ferritin and MMP-9 levels showed higher values in the infected group but did not reach statistical significance (p = 0.076 and p = 0.094, respectively). The combination of CRP, D-dimer, WBC, sCD14, and SAA demonstrated 90% sensitivity and 92% specificity for PJI detection. Conclusion: Continuous monitoring of CRP, D-dimer, WBC, sCD14, and SAA offers a reliable approach for early detection of PJI in osteoporotic patients undergoing hip arthroplasty. These markers showed strong associations with infection, while ferritin and MMP-9 were less informative. This strategy may help improve early diagnosis and patient outcomes.